STAT6 Pathway Is Critical for the Induction and Function of Regulatory T Cells Induced by Mucosal B Cells - Chu, Kuan-Hua; Lin, Szu-Yu; Chiang, Bor-Luen (Frontiers in Immunology, 2021)
B cells could convert naïve T cells into regulatory T cells (so-called Treg-of-B cells) which have the ability to treat animal models of inflammatory diseases, including allergic asthma, collagen-induced arthritis and colitis; however, the mechanisms of Treg-of-B cell generation remain unclear. In this study, we investigated the role of STAT6 in the generation of Treg-of-B (P) cells, which Treg cells were generated by Peyer’s patch B cells (P stands for Peyer’s patch). CD4+CD25- T cells from wild type, STAT6 knockout and IL-4 knockout mice were cocultured with wild type Peyer’s patch B cells for Treg-of-B (P) cell generation. A murine asthmatic model was used to analyze the in vivo regulatory function of Treg-of-B (P) cells. The data demonstrated that STAT6 played a critical role in the generation of Treg-of-B (P) cells, which confirmed with STAT6-deficient T cells and the STAT6 inhibitor AS1517499. When STAT6 was lacking, Treg-of-B (P) cells exerted impaired suppressive ability with decreased LAG3 expression. Furthermore, Peyer’s patch B cells played an essential role in regulatory T cell generation. In the absence of Peyer’s patch B cells, T cells expressed decreased phosphorylated STAT6, which was followed by decreased LAG3 expression and impaired suppressive ability, suggesting that Peyer’s patch B cells provided the critical signal to activate STAT6 phosphorylation in T cells. Moreover, STAT6 deficient Treg-of-B (P) cells could not alleviate inflammation in an animal model of asthma in vivo. IL-4 was downstream of phosphorylated STAT6 and maintained Treg-of-B (P) cell survival with increased expression of Bcl-2 and BclXL. We reported a novel finding that the STAT6-LAG3 signaling axis is important for the induction and function of Treg-of-B (P) cells.